Upaya Preventif untuk Menurunkan Intensi Merokok Pada Remaja Melalui Program "Peduli Diri" - Rohmadani, Zahro Varisna (2016)
This study aims to determine the effectiveness of the "Self Care" program and psychoeducation as a preventive effort to reduce teen smoking intentions. The subjects are 21 students; 7 students belonging to the experimental as group I, 7 students belonging to the experimental as group II and 7 other students joined in the control group. Characteristics of the subjects are: 1) students who score smoking moderate intention to high, 2) aged 12-18 years, 3) willing to sign a contract and become an active participant as well as charge sheet of informed consent, 4) never completing the "Self Care" program or psychoeducation and does not take any treatment on smoking during the subject of research. The experimental group I get a treatment "Self Care" program in the form of psychoeducation and self-control techniques for 365 minutes, while the experimental group II receives treatment in the form of psychoeducation for 130 minutes. Experimental designs used are multiple treatment and control with pretest. Collecting data in this study is conducted using the smoking scale intention. Data analysis method used is nonparametric statistical techniques by using Kruskal Wallis to test the differences in three groups, whereas in each group uses the Wilcoxon Signed Rank Test. Results Kruskal Wallis test showes that there are differences between the groups given in the "Self Care" program, psychoeducation, and control, which the most widely declining level of the intention of smoking is group given psychoeducation with the mean rank of 17.5, and a group given the "Self Care" program mean rank 11.21 and 4.29. Wilcoxon Signed-Rank Test showes that the "Self Care" program and psychoeducation is effectively lower adolescent smoking intentions with each p = 0.018 and a control group that is not subjected to the treatment has no intention of smoking decreased (p = 0.551). The conclusion of this analysis is that psychoeducation is more effective in reducing teen smoking intention than the "Self Care" program.